2017
DOI: 10.1371/journal.pone.0178694
|View full text |Cite
|
Sign up to set email alerts
|

Unconscious improvement in foreign language learning using mismatch negativity neurofeedback: A preliminary study

Abstract: When people learn foreign languages, they find it difficult to perceive speech sounds that are nonexistent in their native language, and extensive training is consequently necessary. Our previous studies have shown that by using neurofeedback based on the mismatch negativity event-related brain potential, participants could unconsciously achieve learning in the auditory discrimination of pure tones that could not be consciously discriminated without the neurofeedback. Here, we examined whether mismatch negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 35 publications
0
19
2
1
Order By: Relevance
“…The individual auditory discrimination threshold was used as the deviation stimulus in our study while a previous study used a fixed frequency as the deviation parameters. Some of our results are inconsistent with the previous data, and the discrepancy may be caused by different paradigm parameters of the experimental design (Chang et al, 2014 , 2017 ). Considering that the MMN index discrimination of various sound stimuli can result from a rigid matching similar to behavioral discrimination, the MMN signals are associated with the magnitude of deviation and involve perceptual discriminability (Näätänen et al, 2017 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The individual auditory discrimination threshold was used as the deviation stimulus in our study while a previous study used a fixed frequency as the deviation parameters. Some of our results are inconsistent with the previous data, and the discrepancy may be caused by different paradigm parameters of the experimental design (Chang et al, 2014 , 2017 ). Considering that the MMN index discrimination of various sound stimuli can result from a rigid matching similar to behavioral discrimination, the MMN signals are associated with the magnitude of deviation and involve perceptual discriminability (Näätänen et al, 2017 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies in 2014 have shown that MMN neurofeedback training can improve discrimination between very similar tones, such as “1,000 Hz” and “1,008 Hz” by Chang et al ( 2014 ). A study published in 2017 used MMN neurofeedback to successfully discriminate the English pronunciation between the letters “l” and “r” to facilitate the foreign language learning (Chang et al, 2017 ). These studies focused on the use of learning to discriminate the targeting of the similar stimuli, similar to discrimination between standard and deviant stimuli during the neurofeedback training to elicit MMN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…test was assessed with a 2AFC (Two-alternative forced choice) task to evaluate subjective /l/-/r/ auditory distinguishing ability (lrADA) in advance of the pupillometry experiment. The word sets used in this test were selected by referring to the experiment by Chang et al 6 . Twenty speech synthesized English words including phoneme /l/ and /r/ each, were generated and controlled in the same way as the experiment stimuli.…”
Section: Procedure Behavioural Auditory Distinguishing Ability Testmentioning
confidence: 99%
“…Speech synthesized stimuli pair "light" /lάit/ or "right" /rάit/ by a female speaker were presented as either the standard sound, which is frequently presented, or as the deviant sound, which is the target stimuli in the oddball paradigm. The stimuli and procedure are based on the previous study focusing on auditory English distinction combined with EEG measurement technologies 6 . The two stimuli were presented in pseudo-randomized order, the oddball stimuli presented in low frequency were controlled not to be presented continuously.…”
Section: Procedure Behavioural Auditory Distinguishing Ability Testmentioning
confidence: 99%